Teaching elementary mathematics to struggling learners - Witzel, Bradley S.; Little, Mary E. (Professor of education) (New York London The Guilford Press, 2016)
Packed with effective instructional strategies, this book explores why certain K-5 students struggle with math and provides a framework for helping these learners succeed. The authors present empirically validated practices for supporting students with disabilities and others experiencing difficulties in specific areas of math, including problem solving, early numeracy, whole-number operations, fractions, geometry, and algebra. Concrete examples, easy-to-implement lesson-planning ideas, and connections to state standards, in particular the Common Core standards, enhance the book's utility. Also provided is invaluable guidance on planning and delivering multi-tiered instruction and intervention.
Introduction -- 1. Foundations of mathematics education -- 2. The critical importance of instruction -- 3. The language of mathematics -- 4. Number sense -- 5. Whole-number operations -- 6. Rational-number concepts and computation -- 7. Geometry and measurement -- 8. Algebra -- 9. Multi-tiered systems of supports in mathematics
Includes bibliographical references (pages 167-175) and index.
Keywords: Mathematics -- Study and teaching (Elementary); Learning disabled children